The zebrafish : disease models and chemical screens - Detrich, H. William, III; Westerfield, Monte; Zon, Leonard I. (Methods in cell biology ;, 2011)
This volume of Methods in Cell Biology is the 3e, and provides comprehensive compendia of laboratory protocols and reviews covering all the new methods developed since 2004. This new volume on Disease Models and Chemical Screens, covers two rapidly emerging and compelling applications of the zebrafish. * Details state-of-the art zebrafish protocols, delineating critical steps in the procedures as well as potential pitfalls * This volume concentrates on Disease Models and Chemical Screens.